Perang Global Terhadap Terorisme Sebuah Tinjauan Benturan Ideologi Barat dan Islam Pasca Perang Dingin - Harlis, Syukri Alfauzi; , Dr. Aidul Fitriciada Azhari, SH., M.Hum; , Dr. Syamsul Hidayat, M.Ag (2015)
The issue of terrorism becomes a trend and actual news among the public in general, but its existence has created a public opinion that is enough to discredit moslem People, where every information associated with terrorism is always associated with Muslims, and in the level of implementation of the policy of the Islamic world becomes the target attack US military aggression, with various other Islamic countries, including Indonesia, where Muslims are always the victims behind the policy field. This has caused fear itself for Muslims because it is always suspected of being terrorists. The Impactalso large enough for the unity of Muslims and has given rise to Islamophobia among non-Muslims. therefore, the purpose of this study tried to find the thread behind the creation of a war of terrorism, so that Muslims can understand the reality of what actually happened, and assess issues related to terrorism are always associated with Muslims. This study includes qualitative nature library research , with descriptive analytical approach . The sources of data used in this study are primary and secondary , and not using field research . The type of data archives here shaped the birth policy of war against terrorism and several scientific papers or journals as well as previous studies either thesis or dissertation related to terrorism or discussed ways the relationship between Islam and the West . Based on an analysis assisted by civilization clash theory approach by Samuel P. Huntington , it can be understood , that there is actually a clash of ideology that occurred between the West and Islam , and a sense of threat and fear felt by the West in realizing the ideals his ideology . US In an effort to realize that need a strategic, and it was realized with the momentum of 9/11 , which has spawned a global war against terrorism decree , receive specific is mentioned al Qaeda and radical extremist Islamic groups and everything that could threaten US interests . key words: Islam, Terrorist, Ideology and US.